Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content: 1. School Principals’ Practice of Knowledge Management in the Wilayat of Saham in North Batinah Governorate from the Point of View of Teachers Amal Salim Alshidi, Dr. Mohammed Abdullah Al-Nofli 2. The level of cyberbullying and its impact on the academic achievement of male and female secondary school students in Riyadh from their point of view Arwa Abdullah Aljasser 3. Developing educational supervision in light of the quantitative and qualitative growth of educational supervisors and teachers in the city of Riyadh Ali Yahya Jarrah, Muhammad Nasser Albaqih 4. The degree of availability of the learning organization dimensions in light of the Senge model in general education schools Reem Mohammed Al Maawy, Hanan Hassan Alghamdi 5. The Impact of the Teaching Competence of Science Teachers and Their Attitudes Towards the Role of the Teacher Preparation Program for the Basic Stage in Khartoum Taghreed Mohamed Yousif